Dichloro-Diphenyl-Trichloroethane and Benzene Hexachloride Metabolite Residues in Blood of Khat (Catha edulis) Chewers and Agricultural Workers in Wondogenet district, Sidama National Regional State, Ethiopia - S. R. Sisay; S. S. Solomon; T. Y. Girma; S. B. Yohannes; A. G. Asamire; T. B. Liya; E. Amanuel (Journal of Applied Sciences and Environmental Management)
Ethiopia is the world’s largest producer and exporter of khat. However, pesticides are used intensively to protect khat from destruction of pest and increase its product, which is leading exposure to agricultural workersandkhat chewers.  The objective of this paper was to evaluate the levels of Dichloro-Diphenyl-Trichloroethane (DDT) and Benzene Hexachloride (BHC) Metabolite Residues in Blood samples of Khat (Catha edulis) Chewers and Agricultural Workers in Wondogenet district, Sidama National Regional State, Ethiopia using appropriate standard techniques. Data obtained show that in chewers blood samples the concentration was ranked as follows: p,p’-DDE (14.26µgL-1) >p,p’-DDT(5.88µgL-1) > Gamma BHC (3.378µgL-1)  >Beta BHC (2.336µgL-1)>Delta BHC (0.506 µgL-1).Whereas ,in sprayer workers the concentration was ranked as follow:p,p’-DDE (13.245µgL-1) >p,p’-DDT(5.468 µgL-1) > Gamma BHC (3.13µgL-1)  >Beta BHC (2.169 µgL-1) >Delta BHC (0.469 µgL-1) and in farmers blood sample the concentration of pesticides was as follow;p,p’-DDE (0.193µgL-1) >p,p’-DDT(0.192µgL-1) > Gamma BHC (0.11µgL-1)  >Beta BHC (0.07µgL-1) >Delta BHC (0.02µgL-1).There is significant difference in mean concentration of delta BHC,gammaBHC,betaBHC,,ppDDE and ppDDT in blood serum among spray workers and farmers as well as khat chewers and farmers.Furthermore, onepesticides:ppDDE had residues above ADI in blood serum of khat chewers and spray workers.Therefore, vigilant monitoring pesticide levels in khat is imperative for addressing environmental and public health concerns. It is essential for policymakers to take appropriate measures at this critical time to safeguard public health against the threats posed by pesticide pollution in Khat cultivation.